2020
DOI: 10.3390/diagnostics10090665
|View full text |Cite
|
Sign up to set email alerts
|

Identification the Cross-Reactive or Species-Specific Allergens of Tyrophagus putrescentiae and Development Molecular Diagnostic Kits for Allergic Diseases

Abstract: Mite allergens are considerable factors in the genesis of allergic diseases. The storage mite Tyrophagus putrescentiae (Tp) appears in contaminated foods and household surroundings. The current diagnostic tools for Tp allergy are mostly based on crude extracts and still contain shortcomings. This study aimed to investigate the immunoglobulin E (IgE)- responsiveness profiles of Tp-allergic patients and develop a molecular diagnostic method using recombinant allergens. Allergenic components were characterized as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Tyrophagus putrescentiae sensitization has been reported in Europe and Asia, and its clinical relevance, particularly in elderly subjects, is increasingly recognised [ 49 ]. Although co-sensitisation to Dermatophagoides pteronyssinus and/or Dermatophagoides farina is common among patients with sensitivity to Tyrophagus putrescentiae [ 50 , 51 ], we are unaware of any studies addressing the molecular composition of mopane worms versus Tyrophagus putrescentiae. We speculate cross-reactive recognition of the two allergen sources as an explanation for the consistently high levels of T. putrescentiae reactivity in contrast with reactivity to D. pteronyssinus and D. farinae.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrophagus putrescentiae sensitization has been reported in Europe and Asia, and its clinical relevance, particularly in elderly subjects, is increasingly recognised [ 49 ]. Although co-sensitisation to Dermatophagoides pteronyssinus and/or Dermatophagoides farina is common among patients with sensitivity to Tyrophagus putrescentiae [ 50 , 51 ], we are unaware of any studies addressing the molecular composition of mopane worms versus Tyrophagus putrescentiae. We speculate cross-reactive recognition of the two allergen sources as an explanation for the consistently high levels of T. putrescentiae reactivity in contrast with reactivity to D. pteronyssinus and D. farinae.…”
Section: Discussionmentioning
confidence: 99%
“…At least 20 kinds of IgE-binding allergenic components of T. putrescentiae have been detected in allergic patient’s sera ( 74 ). Although allergen-specific CD4 + Th2 cells instigate the allergic responses, notably through the production of IgE directed towards mite allergens, recent studies have demonstrated that innate immune activation also plays an important role in mite-induced allergy pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although co-sensitisation to Dermatophagoides pteronyssinus and/or Dermatophagoides farina is common among patients with sensitivity to Tyrophagus putrescentiae (50,51), we are unaware of any studies addressing the molecular composition of mopane worms versus Tyrophagus putrescentiae. We speculate cross-reactive recognition of the two allergen sources as an explanation for the consistently high levels of T. putrescentiae reactivity in contrast with reactivity to D. pteronyssinus and D. farinae.…”
Section: Discussionmentioning
confidence: 99%